2021
DOI: 10.3390/ijms22147293
|View full text |Cite
|
Sign up to set email alerts
|

Small Leucine-Rich Proteoglycans (SLRPs) in the Retina

Abstract: Retinal diseases such as age-related macular degeneration (AMD), retinopathy of prematurity (ROP), and diabetic retinopathy (DR) are the leading causes of visual impairment worldwide. There is a critical need to understand the structural and cellular components that play a vital role in the pathophysiology of retinal diseases. One potential component is the family of structural proteins called small leucine-rich proteoglycans (SLRPs). SLRPs are crucial in many fundamental biological processes involved in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…A proteomics study of postmortem human eyes revealed that lumican was also found in Bruch's membrane, the choroid, and neurosensory retinae [30], where it was highly associated with ERM's origin. Due to being a member of the class II small leucine-rich proteoglycan (SLRP) family, lumican can maintain retinal homeostasis, is involved in collagen fibrillogenesis, and regulates proinflammatory responses [31]. Animal studies also proved increased expression of lumican along with age and modifications of lumican by macrophages, neutrophils, and polymorphonuclear neutrophils in immune responses [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A proteomics study of postmortem human eyes revealed that lumican was also found in Bruch's membrane, the choroid, and neurosensory retinae [30], where it was highly associated with ERM's origin. Due to being a member of the class II small leucine-rich proteoglycan (SLRP) family, lumican can maintain retinal homeostasis, is involved in collagen fibrillogenesis, and regulates proinflammatory responses [31]. Animal studies also proved increased expression of lumican along with age and modifications of lumican by macrophages, neutrophils, and polymorphonuclear neutrophils in immune responses [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of decorin significantly inhibits laser induced CNV in a rodent model [ 223 ]. Decorin might exhibit anti-angiogenic responses by acting as an inhibitor for multiple receptor tyrosine kinases, such as the epidermal growth factor receptor (EGFR), the insulin-like growth factor receptor (IGFR), and the Met hepatocyte growth factor receptor [ 224 ]. It has also been shown to decrease hypoxia-induced VEGF expression by blocking the Met expression pathway and downregulating the Ras-related C3 botulinum toxin substrate and HIF1-α [ 224 ].…”
Section: Damps In Retinal Disordersmentioning
confidence: 99%
“…Decorin might exhibit anti-angiogenic responses by acting as an inhibitor for multiple receptor tyrosine kinases, such as the epidermal growth factor receptor (EGFR), the insulin-like growth factor receptor (IGFR), and the Met hepatocyte growth factor receptor [ 224 ]. It has also been shown to decrease hypoxia-induced VEGF expression by blocking the Met expression pathway and downregulating the Ras-related C3 botulinum toxin substrate and HIF1-α [ 224 ]. Additionally, the RPE cells with a high-risk genotype at 10q26 for AMD showed significantly enhanced versican expression in the ECM [ 206 ].…”
Section: Damps In Retinal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in exploring N -glycans’ role in AMD stems from the understanding that various proteoglycans have a role in retinal development and functioning [ 20 , 21 , 22 ], suggesting that their manipulation may even have beneficial therapeutic effects [ 23 ]. This was seen for NA3, a tri-antennary glycan without sialic acid, which was implied as having a protective role in AMD pathogenesis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%